Job Satisfaction Among Academic and Administrative Staff in Universiti Malaysia Sarawak (Sains Humanika, 2012)
This study investigated the levels of job satisfaction of academic and administrative staff of University Malaysia Sarawak (UNIMAS) across six dimensions of job satisfaction. It employed a cross-sectional survey research design involving 59 academic and administrative staff from UNIMAS. The six dimensions of promotion, supervision, work itself, colleagues, work environment, and pay benefits were used to measure the level of job satisfaction. On the whole, both academic and administrative staff in UNIMAS enjoyed modest level of satisfaction. There were no significant differences in the level of satisfaction in all dimensions except work itself, where it was found that academic staff tended to enjoy higher level of job satisfaction compared to administrative staff. Gender and disciplines (field of expertise) were not significant factors in influencing job satisfaction. The findings from the study generally supported past findings in the literature. As job satisfaction amongst the academic and administrative staff in UNIMAS were relatively modest, UNIMAS management should consider ways to improve the level of job satisfaction of its staff along the six dimensions investigated, irrespective of gender, disciplines and job categories (academic and non-academic). The study could be extended to other local universities to see if similar patterns exist and thus enable the Ministry of Higher Education (MOHE) to look into relevant human resource policies to enhance job satisfaction amongst academicians and administrative staff in the public universities.
Keywords: Job satisfaction; academic staff; administrative staff; university